Klasifikasi Daya Tarik Wisata Unggulan Provinsi Bengkulu Sebagai Upaya Menyongsong Visit 2020 Wonderful Bengkulu - Saputri, Dwi Oktavallyan; Ta’alidin, Zamdial; Prihatiningrum, Atik (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 01, Juli 2019DO - 10.24843/JUMPA.2019.v06.i01.p03, 2019)
Bengkulu Province has begun to aware to its tourism potential, hence a program called "Visit 2020 Wonderful Bengkulu" was conducted and held by all Regencies / Cities of Bengkulu Province. Bengkulu Province has tremendous tourism potential to be developed, thus it is necessary to classify leading tourist attractions in an effort to support the program. The research method used is descriptive qualitative and quantitative, namely describing observations through field observations and direct assessments using the Tourism Attraction Assessment Guidelines in a systematic and actual procedure. The results is Bengkulu Province has few potential tourism, however, in general the potential is still not balanced by the availability of adequate accessibility and facilities / amenities. Almost all tourist attractions in 10 regencies / cities in Bengkulu Province in general are still insufficient in the management, planning and developing tourism. This research is expected to become a guideline in the tourism development of Bengkulu Province in preparing to welcome the "Visit 2020 Wonderful Bengkulu" program. Keywords: Potential, Tourist Attraction, Bengkulu